Blefarospasmo essencial e espasmo hemifacial: Características dos pacientes, tratamento com toxina botulínica A e revisão da literatura - Schellini, Silvana Artioli [UNESP]; Matai, Olívia [UNESP]; Igami, Thais Zamudio [UNESP]; Padovani, Carlos Roberto [UNESP]; Padovani, Carlos Pereira [UNESP] (FapUNIFESP (SciELO), 2006)
Purpose: To evaluate the characteristics of the essential blepharospasm and hemifacial spasm patients and the feasible treatment with botulinum toxin. A. Methods: Thirty-four essential blepharospasm or hemifacial spasm patients were evaluated according to gender, ocular complaint, time of disease, treatment outcome and complications. Results: Age median was 63 years and the mean was 61 years, with no difference regarding sex; 66.66% of the patients had hemifacial spasm and 33.33%, essential blepharospasm. Many patients complained of dry eye associated with involuntary spasm. Botulinum toxin A showed a positive outcome in 91.30% of the treated patients and complications observed after treatment were eyelid ptosis (8.33%) and buccal angle deviation (8.33%). Conclusion: Essential blepharospasm and hemifacial spasm occurred in the elderly, of both sexes. Treatment with botulinum toxin A was useful, with very low complication rates.
Essential blepharospasm and hemifacial spasm: Characteristic of the patient, botulinum toxin A treatment and literature review
Keywords: Action potentials; Blepharospasm/drug therapy; Botulinum toxin type A/therapeutic use; Hemifacial spasm/drug therapy; Oculomotor muscles; botulinum toxin A; adult; blepharospasm; cheek mucosa; clinical article; clinical feature; controlled study; dry eye; feasibility study; female; gender; hemifacial spasm; human; male; ptosis; review; treatment outcome; Adult; Aged; Blepharospasm; Botulinum Toxin Type A; Female; Hemifacial Spasm; Humans; Male; Middle Aged; Neuromuscular Agents; Treatment Outcome